IS PILOT TESTING AN INDICATOR OF STUDENTS’ PERFORMANCE? - Rosaroso, Rufina C. (European Scientific Journal, ESJ, 2015)
This study assessed the average or typical performance of selected fourth year high school students in a proposed University of San Carlos College Admission and Placement Test (USCCAPT) in Cebu City, Philippines. The college admission test is an aptitude test which is a locallymade admission and placement test composed of 259 items for all college freshman applicants. Item development was done by the different department representatives from various departments, namely; English, Mathematics, Biology, Chemistry, Physics and Psychology. Content-related validity evidence was initially established through the development of test’s Tables of Specifications and a systematic review of its content and objectives based on experts’ judgment. Pilot testing was administered to selected high school students who served as samples of the study. Computation of students’ mean scores per school and their quartile ranks were used as methods of data analysis. Further, item analysis was utilized to assess the degree of difficulty, discrimination and effectiveness of the constructed items.